Smartphone adapters for flexible Nasolaryngoscopy: a systematic review - A. E. Quimby; S. Kohlert; L. Caulley; M. Bromwich (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Flexible nasolaryngoscopy is an essential component of the otolaryngological physical exam. Historically, the ability to create and share video recordings of these endoscopic exams has been limited by poor mobility of fixed endoscopy towers. The advent of smartphone endoscope adapters has allowed physicians to create and share video recordings of endoscopy in a wide variety of locations that would not have previously been feasible. This paper sought to review the literature on the effect of smartphone endoscope adapters on patient care, patient satisfaction, and resident learning. Methods This systematic review was conducted according to PRISMA guidelines. A systematic literature search was performed for all relevant English language studies (1946–2017) using Ovid MEDLINE, PubMed, and EMBASE. The study protocol was registered with the PROSPERO database. Results A total of 91 abstracts were identified and screened by two independent reviewers. Based on inclusion and exclusion criteria, three studies were selected and subjected to full-text extraction as well as quality assessment. These studies demonstrated high diagnostic accuracy and quality of smartphone adapter-recorded videos, and a benefit of these devices on resident education. Due to the heterogeneity of included studies’ methods and measures, a meta-analysis was not possible, so a qualitative synthesis of the literature results was performed. Conclusion Despite a paucity of data on the subject, the present study provided a comprehensive review of the literature, and suggested overall high diagnostic accuracy, quality, and enhancement of resident education with the use of smartphone endoscope adapters for flexible nasolaryngoscopy. Trial registration CRD42018086714.